PRMT9 promotes hepatocellular carcinoma invasion and metastasis via activating PI3K/Akt/GSK‐3β/Snail signaling. Issue 5 (May 2018) - Jiang, Hai; Zhou, Zhenyu; Jin, Shaowen; Xu, Kang; Zhang, Heyun; Xu, Junyang; Sun, Qing; Wang, Jie; Xu, Junyao
Abstract : Protein arginine methyltransferases (PRMT) catalyze protein arginine methylation and play an important role in many biological processes. Aberrant PRMT expression in tumor cells has been documented in several common cancer types; however, its precise contribution to hepatocellular carcinoma (HCC) cell invasion and metastasis is not fully understood. In this study, we identified a new oncogene, PRMT9, whose overexpression strongly promotes HCC invasion and metastasis. PRMT9 expression was detected more frequently in HCC tissues than in adjacent noncancerous tissues. PRMT9 overexpression was significantly correlated with hepatitis B virus antigen (HBsAg) status, vascular invasion, poor tumor differentiation and advanced TNM stage. Patients with higher PRMT9 expression had a shorter survival time and higher recurrence rate. PRMT9 expression was an independent and significant risk factor for survival after curative resection. Functional studies demonstrated that PRMT9 increased HCC cell invasion and lung metastasis. Knocking down PRMT9 with short hairpin RNA (shRNA) inhibited HCC cell invasion. Further investigations found that PRMT9 increased cell migration and invasion through epithelial‐mesenchymal transition (EMT) by regulating Snail expression via activation of the PI3K/Akt/GSK‐3β/Snail signaling pathway. In clinical HCC samples, PRMT9 expression was positively associated with Snail expression and was negatively associated with E‐cadherin expression. In conclusion, our study demonstrated that PRMT9 is an oncogene that plays an important role in HCC invasion and metastasis through EMT by regulating Snail expression via activation of the PI3K/Akt/GSK‐3β/Snail signaling pathway. Thus, PRMT9 may serve as a candidate prognostic biomarker and a potential therapeutic target. Abstract : This study is the first to demonstrated that PRMT9 is an oncogene that plays an important role in HCC invasion and metastasis through EMT by regulating Snail expression via activation of the PI3K/Akt/GSK‐3β/Snail signalling pathway. Thus, PRMT9 may serve as a candidate prognostic biomarker and a potential therapeutic target.